Covid-19, monkeypox, and others when will new infectious diseases stop emerging - Ahmad Mahfuz, Gazali (Social Health Analytics Sdn Bhd, 2022)
In this day and age, new infectious diseases will continue to emerge, and we will hear about it sooner rather than later.